Exploration of Cytotoxicity and Anti-tumor Activity of Manilkara hexandra Leaves on Ehrlich Ascites Carcinoma Model : Cytotoxicity and antitumour activity of Manilkara hexandra leaves - Hegde, Medha Mohan; Lakshman, K (Iranian Journal of Pharmaceutical Sciences, 2025)
Manilkara hexandra (Sapotaceae) is an evergreen, medium-sized tree that grows in tropical and temperate regions. The different parts of this plant are traditionally used as an expectorant, antileprotic, febrifuge, purgative, aphrodisiac, and anthelmintic. At dosages of 50, 100, 200, 400, and 800 µg/mL, the anti-cancer efficacy of the ethanolic extract of Manilkara hexandra (EELMH) against Ehrlich Ascites Carcinoma (EAC) cells was evaluated using MTT and trypan blue assays. It exhibited a cytotoxic effect with IC50 values of 612 µg/mL and 624.97 µg/mL in MTT and trypan blue assays, respectively, after 48 hours. DAPI staining after treating the EAC cells at an IC50 value of 612 µg/ml showed morphological changes in the nucleus. The further anti-tumor activity of EELMH was evaluated in vivo using EAC-bearing Swiss albino mice at 200 and 400 mg/kg body weight. The effect of EELMH on tumor growth, cell viability, lifespan, hematological, and biochemical parameters of EAC-bearing mice was assessed. In addition to extending the lifespan of EAC-bearing mice, EELMH demonstrated a significant reduction in tumor volume, packed cell volume, and viable cell count. The hematological and serum biochemical parameters returned to nearly their original levels in mice treated with EELMH, specifically at a dose of 400 mg/kg.